Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd005943.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen for treating threatened miscarriage

Abstract: Analysis 1.3. Comparison 1 Progestogens versus placebo or no treatment, Outcome 3 Pregnancy-induced hypertension. Analysis 1.4. Comparison 1 Progestogens versus placebo or no treatment, Outcome 4 Antepartum haemorrhage.. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 45 publications
1
41
0
6
Order By: Relevance
“…As well as inducing secretory changes in the endometrium during the luteal phase that promote implantation and support early pregnancy [5,6], it modulates the maternal immune response to prevent foetal rejection [7] and relaxes the uterine smooth musculature [8]. Despite this physiological evidence, which has led to progestogens being used in the management of threatened miscarriage for many years, there is little data available from well designed and well controlled clinical trials to support their routine use in this indication [9].…”
Section: Introductionmentioning
confidence: 99%
“…As well as inducing secretory changes in the endometrium during the luteal phase that promote implantation and support early pregnancy [5,6], it modulates the maternal immune response to prevent foetal rejection [7] and relaxes the uterine smooth musculature [8]. Despite this physiological evidence, which has led to progestogens being used in the management of threatened miscarriage for many years, there is little data available from well designed and well controlled clinical trials to support their routine use in this indication [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sekitar 50-60% abortus dapat disebabkan oleh karena adanya kelainan kromosom janin, infeksi, kelainan endokrin, dan kelainan anatomi uterus, dan sekitar 40-50% belum bisa dijelaskan. 2 Abortus iminens ditandai oleh perdarahan vaginal pada kehamilan trimester pertama, dengan atau tanpa nyeri perut dan serviks masih tertutup serta janin masih viabel dan berada di dalam uterus. Ketika serviks mulai berdilatasi, abortus atau kegagalan kehamilan tidak akan terelakkan.…”
Section: Pendahuluanunclassified
“…A recent Cochrane meta-analysis including 4 studies and 421 participants found a reduction in the rate of threatened abortion by the use of progesterone compared with placebo or no treatment (risk rate: 0.53; 95% CI: 0.35-0.79) [114].…”
Section: Progesterone To Prevent Miscarriagementioning
confidence: 99%